Environmental Regulations and Energy Efficiency: The Mediating Role of Climate Change and Technological Innovation - Wang, Peng; Liang, Shuai (Frontiers in Environmental Science, 2022)
Low-carbon energy transformation increases energy efficiency, and environmental regulation is necessary for carbon neutrality As a cost-effective method of reducing air pollution and improving the economic performance of manufacturing industries, energy efficiency is widely accepted. In order to make their manufacturing sectors more energy efficient, a large number of countries have implemented legislation. It is possible to tailor these interventions to a specific company or industry by using measures to control and direct or interventions in the marketplace. These policies might be beneficial, but experiential study of the impacts of these interferences on energy-saving technology acceptance have not been conclusive. There are many environmental policy measures that have an effect on the level of asset in energy efficiency machineries. The years 2010–2017 are covered in this research, which compiles a database of Spanish industries from various sources. As a result, we have access to a wide range of factors and strategy devices that could influence the adoption of energy efficiency measures. Regulation, taxes, subsidies, and exemptions are among the instruments we'll examine. These findings support the development of environmental regulations in China that will further improve energy efficiency and carbon neutrality.